1991
DOI: 10.1183/09031936.93.04020191
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to evaluate lung aggression in monkey silicosis: hydrolases, peroxidase and antiproteases activities in serial bronchoalveolar lavages

Abstract: Exposure to silica can induce fibrosis and/or emphysema. Various factors such as proteases, other hydrolases and oxidants may be involved in the destruction of lung parenchyma. On the other hand, antiproteases play an important role in the protection of lung parenchyma against the action of proteases. We have developed an animal model of silicosis in monkey Macacus cynomolgus and followed these factors by bronchoalveolar lavage (BAL). We have studied glycosidases activities, elastase-like activity, immunoreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This question has not been extensively investigated. Brown et al (12) showed that there were increases in lavage proteolytic activity from rats given quartz or titanium dioxide, but Hannothiaux et al (13) found only small and inconsistent increases in lavage elastase activity from monkeys administered quartz. Rom (14) reported increased levels of elastase complexed to AlAT in lavages from coal miners.…”
Section: Introductionmentioning
confidence: 99%
“…This question has not been extensively investigated. Brown et al (12) showed that there were increases in lavage proteolytic activity from rats given quartz or titanium dioxide, but Hannothiaux et al (13) found only small and inconsistent increases in lavage elastase activity from monkeys administered quartz. Rom (14) reported increased levels of elastase complexed to AlAT in lavages from coal miners.…”
Section: Introductionmentioning
confidence: 99%
“…At present, animal models are widely used for the reproduction of all different types of human diseases, allowing the deeper study of physical and pathological mechanisms and the search for new therapies and treatments. Silicosis can occur spontaneously in nature and many cases have been reported in numerous mammalian species such as pigs [ 66 ], dogs [ 67 ], camels [ 68 ], horses [ 69 , 70 ], nonhuman primates [ 71 ], river otters [ 72 ] and marsupials [ 73 ]. It has also been found in various species of birds like ground dwelling kiwi ( Apteryx spp.)…”
Section: Animal Models Of Silicosismentioning
confidence: 99%